From Tunisian Women Film Pioneer to the Jasmine Generation: Rights, Body and Resistance - Cubero, Alejandra Val (Comunicación y Género [Communication and Gender], 2021)
The greater freedom of expression that exists in Tunisia after the Revolution of 2011 has given rise to a great cultural upheaval that has been felt fully felt in women’s cinema. The echoes come from far away and we should go back to the first generation of Tunisian women directors such as Selma Baccar, Néjia Ben Mabrouk, Kalthoum Bornaz or Moufida Tatli, who started shooting very critical films in the 1970s about gender inequalities, male domination and patriarchy; These themes have been picked up and expanded by a new generation of female directors who emerged at the dawn of the Arab Revolution or Jasmine Revolution, women who, without forgetting the issues that intrigued their predecessors, they are in dialogue with aspects that are still taboo in Arab-Muslim societies, such as the body, sexuality and religion. Nowadays Islamophobia is growing in the West and highlighting the way women filmmakers in Tunisia fought and fight through their works for a more egalitarian society is of great importance, not only to understand their culture, but also to understand our culture in a better way.